Response of different wheat varieties to Bipolaris sorokiniana at seedling stage under laboratory condition - Kandel, Khagendra; Dhakal, Dilli; Giri, Harish; Basnet, Sushil; Koirala, Utsav; Dhakal, Narayan (Journal of Agriculture and Natural Resources, 2020)
Spot blotch (Bipolaris sorokiniana) is a major disease of wheat in warm, humid wheat-growing regions. The aim of present study was to evaluate the infection symptomology and disease severity to different wheat varieties under laboratory condition. A total of ten wheat genotypes including RR-21 (a susceptible check) and Aditya (a resistant check), were evaluated for seedling stage resistance to spot blotch disease through artificial inoculation under laboratory condition at Gokuleswor, Baitadi during 2018. Based on disease severity and area under disease progress curve (AUDPC), Aditya was found resistant and RR-21 was found susceptible The tested genotypes were categorized on the basis of total AUDPC value, where Banganga, BL4341, BL4407 and local genotype were moderately resistant, BL-4406, NL-1190, NL-297 and NL-971 were found moderately susceptible to spot blot at seedling stage. The susceptible check, RR-21 had the highest disease severity (44%) as well as mean AUDPC value (51.38).